Assessment of dental arches symmetry in a sample of Iraqi children at the mixed dentition stage - Al- Dulayme, Dunia A (Journal of Baghdad College of Dentistry, 2014)
Background: Little is known about asymmetry of children’s dental arches, the purpose of this study was to verify the presence of asymmetry of dental arches among Iraqi children in the mixed dentition stage. Materials and methods: The sample included 52 pairs of dental casts, 27 pairs belong to males and 25 pairs for females. Three linear distances were utilized on each side on the dental arch: Incisal-canine distance, canine-molar distance and incisal-molar distance, which represent the dental arch segmental measurements using the digital sliding calipers, which is accurate up to 0.02 mm. Results: No significant sides’ differences with high correlation coefficient were found between the right and left incisal-canine, canine-molar and incisal-molar distances in both dental arches for both genders with males exhibited higher mean values than females in all segmental measurements of the dental arches. Conclusion: The findings of the present study revealed the symmetrical pattern of dental arches, since statistically the right and left sides showed no significant difference with high correlation coefficient in all measuring segments.